Efektifitas Paket Intervensi Mandiri terhadap Pencegahan Kejadian Stress Urinary Incontinence Post Partum - Maslahatul Inayah; Supriyo Supriyo; Tri Anonim (JURNAL KEPERAWATAN MERSI, 2019)
In labor it will cause the pelvic floor to weaken or become damaged so that it cannot function properly. Urinary incontinence stress is a serious health problem that can appear in the post partum period which can cause both physical and psychological disorders. This study aims to analyze the effectiveness of a package of independent interventions on the prevention of stress urinary incontinence in post partum mothers. This type of research is quantitative research with a quasi-experimental research design with a pre-post test design with a control group. The subject selection was 15 people in the intervention group and 15 in the control group. Bivariate analysis was performed using the Wilcoxon test and Mann-Whitney Test to determine the differences before and after the independent intervention package was given.The results showed that the incidence of stress urinary incontinence in the intervention group decreased from 33.3% to 0% after being given an independent intervention package (p = 0.025), while the incidence of stress urinary incontinence in the control group increased from 26.7% to 53.3 % (p = 1.02). The results of bivariate analysis showed that there were differences in the incidence of stress urinary incontinence post partum in the intervention and control groups before and after being given an independent intervention package (p = 0.011). It is recommended for hospitals to arrange discharge planning to improve patient knowledge in order to prevent stress urinary incontinence.